2020
DOI: 10.1021/acscatal.0c01397
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenase Bioelectrocatalysis: ATP-Independent Ammonia Production Using a Redox Polymer/MoFe Protein System

Abstract: Nitrogenase is the only biological catalyst that is known to be able to convert nitrogen gas to ammonia. In microorganisms, the MoFe catalytic protein of nitrogenase is reduced by a transient Fe protein binding and separate hydrolysis of ATP. However, the requirement of 16 ATP molecules by the Fe protein for the 8 electron transfer is an energy-intense caveat to the enzymatic synthesis of NH3 and is challenging from an electrochemical perspective. Thus, we report the redox polymer-based ATP-free mediated elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…However, when a CdS nanorod replaced the Fe‐protein, lower turnover frequencies were reported (75 min −1 ) . In other reports, using only the MoFe protein, the turnover frequencies are significantly slower 0.1–0.6 min −1 . Therefore, further work is required to improve the rate of catalysis using only the MoFe‐protein.…”
Section: Obstacles and Opportunities For Using Nitrogenase For Energysupporting
confidence: 82%
See 1 more Smart Citation
“…However, when a CdS nanorod replaced the Fe‐protein, lower turnover frequencies were reported (75 min −1 ) . In other reports, using only the MoFe protein, the turnover frequencies are significantly slower 0.1–0.6 min −1 . Therefore, further work is required to improve the rate of catalysis using only the MoFe‐protein.…”
Section: Obstacles and Opportunities For Using Nitrogenase For Energysupporting
confidence: 82%
“…Recently there have been reports of two separate redox mediators, cobaltocene and neutral red being tethered to a polymer for which mediated bioelectrolysis of N 2 reduction to NH 3 was demonstrated.…”
Section: Key Advances In Bioelectrochemistry Of Nitrogenasementioning
confidence: 99%
“…N 2 ase reduces not only N 2 but also nitrite (NO 2 − ) and azide (N 3 − ) to NH 3 on electrodes, and the MoFe protein disassociated with the Fe protein shows the DET-type bioelectrocatalytic activity without ATP [154]. Furthermore, ATP-independent NH 3 bioelectrosynthesis was improved in the MET-type system using N 2 ase and a cobaltocene-functionalized polymeric mediator [51]. On the other hand, Milton et al reported a NH 3 -producing H 2 /N 2 biofuel cell using MET-type reactions of N 2 ase and H 2 ase [148].…”
Section: Ammonia Productionmentioning
confidence: 99%
“…In addition, once both enzymes and mediators are stably immobilized on electrodes, the measurement systems work as pseudo-DET-type systems [10,11,36]. Particularly, redox polymers anchoring osmium complexes [3,[37][38][39][40][41][42][43][44][45], ferricyanide [46,47], metallocenes [48][49][50][51], and viologen units [52][53][54][55] are constructed as polymeric mediators immobilized on electrodes. In summary, a DET-type system is often more ideal than a MET-type system, whereas it seems to be practical to utilize an MET-type system for several objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Die Redoxpolymere wurden ausgewählt, da sie in der Lage sind, Enzyme, die interessante Reduktionsreaktionen katalysieren, [22] elektrisch an Elektroden zu koppeln. Dies wurde kürzlich für P‐vio in Kombination mit Hydrogenasen [12, 23] sowie für verschiedene Cobaltocen‐modifizierte Polymere in Kombination mit Hydrogenasen, [7, 24] Formiatdehydrogenase, [25] Diaphorase für die NADH‐Regeneration [26] und Nitrogenase gezeigt [27] . Die Photostromantwort wurde unter Verwendung von Umgebungs‐O 2 als terminalem Elektronenakzeptor gemessen, wobei die polymergebundenen Redoxzentren einen effizienten Elektronentransfer mit dem terminalen Fe‐S‐Cluster am PSI ermöglichten.…”
Section: Ergebnisse Und Diskussionunclassified